Causes of social conflict in Okky Madasari’s novel 86 based on the perspective of Marxist literary sociology - Arzaqi, Argha Zidan; Al-Furqaan, Dimas Luqman (Universitas Mulawarman, 2025)
Currently, human interactions' dynamics result in the escalation of social conflicts that are becoming increasingly difficult to resolve. The representation of social conflict is frequently illustrated in literary works, as elucidated in the Marxist sociology of literature theory. Therefore, this research aims to describe the causes of social conflict experienced by Arimbi as the main character in novel 86 based on the perspective of Marxist sociology of literature. The method used was descriptive qualitative with a library approach. The method used was descriptive qualitative with a library approach. This research conducts systematic research according to Creswell, specifically by (1) problem statement; (2) literature review; (3) research design; (4) data collection; (5) data analysis; (6) interpretation; and (7) conclusion. This research ‎results in the discovery, namely a portrait of social conflict in the form of troublesome, bribery, discrimination, economic disparity, collusion. The portrayals of social conflict stem from differences in stance, cultural disparities, and varying interests. Every cause of the social conflict originates from the thoughts or desires of individuals belonging to a social class higher than Arimbi. Conversely, as Arimbi's storyline nears its conclusion, she gets entangled in a conflict with the social class beneath her.